Blackbox between job crafting and job embeddedness of immigrant hotel employees: a serial mediation model - Arasli, Huseyin; Arici, Hasan Evrim; Ilgen, Huseyin (Routledge Journals, Taylor & Francis Ltd, 2019)
This study explores the influence of job crafting (JC) on migrant employees? and its sensitivities on job embeddedness (JE) with the application of a serial mediation mechanism which takes into consideration the psychological capital and their work engagement as mediators. The data for this study was collected from immigrant employees in the hotel sector in North Cyprus. Both convenience and judgmental sampling techniques made up of 572 dyads were used. The findings of this study reveal that immigrant employees? psychological capital and their work engagement has a mediating effect on the relationships between organizational crafting and the perceptions of employees? job embeddedness. This study will serve as a substantial research evidence and tool for managers/owners in the hospitality industry for the purpose of retaining, engaging and embedding immigrant employees. The novelty of this study is the fact that it analyzes the work environment and conditions where organizational job crafting affects job embeddedness to determine the perceptions of immigrant employees using a serial mediation model.
Keywords: Job crafting; immigrant employees; psychological capital; work engagement; job embeddedness